Self-Sensing Control of PMSM at Zero and Low Speed - Zossak, Simon; Stulrajter, Marek; Makys, Pavol (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with control of Permanent Magnet Synchronous Motor (PMSM) without a rotor position sensor. In the low and zero speed region, the rotor saliencies are utilized to obtain the information about the rotor position. Self-sensing control techniques employ high frequency (hf) signal injection to excite the saliencies. The proposed algorithm enables tracking the saliency and allows PMSM control at zero and low speed. The theoretical assumptions were experimentally verified including the initial rotor position detection.